Plate boundary deformation and man-made subsidence around geothermal fields on the Reykjanes Peninsula, Iceland - Keiding, Marie; Árnadóttir, Thóra; Jonsson, Sigurjon; Decriem, Judicaël; Hooper, Andrew John (Journal of Volcanology and Geothermal Research, 2010)
We present Interferometric Synthetic Aperture Radar (InSAR) data from 1992-1999 and 2003-2008 as well as GPS data from 2000-2009 for the active plate boundary on the Reykjanes Peninsula, southwest Iceland. The geodetic data reveal deformation mainly due to plate spreading, anthropogenic subsidence caused by geothermal fluid extraction and, possibly, increasing pressure in a geothermal system. Subsidence of around 10. cm is observed during the first 2. years of production at the Reykjanes geothermal power plant, which started operating in May 2006. We model the surface subsidence around the new power plant using point and ellipsoidal pressure sources in an elastic halfspace. Short-lived swarms of micro-earthquakes as well as aseismic fault movement are observed near the geothermal field following the start of production, possibly triggered by the stresses induced by geothermal fluid extraction. © 2010 Elsevier B.V. The ERS and Envisat data were provided by the European Space Agency. We thank Halldor. Geirsson for providing the continuous GPS data, and Halldor Olafsson for skilled and cheerful assistance during numerous GPS campaigns. The earthquake locations, magnitudes and focal mechanisms included in this study are from the SIL seismic catalogue courtesy of the Icelandic Meteorological Office. Pall Jonsson and Gudmundur Omar Fridleifsson provided the pressure data from the Reykjanes geothermal field. We thank Maurizio Battaglia and Yuri Fialko for the codes for computing displacements and stresses due to an ellipsoidal source. Pall Einarsson, Grimur Bjornsson, Ingvar Thor Magnusson and Omar Sigurdsson are thanked for insightful comments. We are also grateful to Thomas R. Walter and an anonymous reviewer for constructive reviews that helped improving the paper. The figures were prepared using the GMT software (Wessel and Smith, 1998). This work is supported by a grant from the Eimskip Fund of the University of Iceland. Funding for GPS equipment used in this study came from the Icelandic Research Fund, the ...